LEGAL REGULATIONS ON CRIMINAL ACTS AGAINST MISUSE OF AI (ARTIFICIAL INTELLIGENCE) TECHNOLOGY IN VOICE PHISHING FRAUD VIA MOBILE PHONES - Yenny Fitri.Z; Alya Alviani (Fakultas Hukum Universitas Djuanda, 2024)
Current technological developments are entering the era of artificial intelligence or what is often referred to as artificial intelligence (AI), this AI technique refers to the simulation of human intelligence on machines that are programmed to think and imitate human actions, but this AI technology can be misused as a criminal act of voice fraud (voice phishing) via mobile phones. This study aims to examine the criminal law regulations regarding the misuse of artificial intelligence in voice phishing using mobile phones. The normative research approach, this study is based on laws and regulations and literature and emphasizes legal norms and principles. The results of this study indicate that the limitations of Law Number 1 of 2024 concerning the second amendment to Law Number 11 of 2008 concerning Information and Electronic Transactions (ITE) have not yet reached this far into criminal acts of voice fraud (voice phishing) via mobile phones and until now criminal acts of voice fraud (voice phishing) via mobile phones are still rampant. Witness and Victim Protection is all efforts made by LPSK or other institutions in accordance with laws and regulations to provide rights and assistance to victims in order to provide a sense of security. To protect the community, legal protection for victims of criminal acts can be carried out in various forms, such as providing restitution and compensation.